Integrase strand transfer inhibitors and neuropsychiatric adverse events in a large prospective cohort. (6th December 2018) - Cuzin, Lise; Pugliese, Pascal; Katlama, Christine; Bani-Sadr, Firouzé; Ferry, Tristan; Rey, David; Lourenco, Jeremy; Bregigeon, Sylvie; Allavena, Clotilde; Reynes, Jacques; Cabié, André; ,
Abstract: Objectives: To analyse the frequency and causes of treatment discontinuation in patients who were treated with an integrase strand transfer inhibitor (INSTI), with a focus on neuropsychiatric adverse events (NPAEs). Methods: Patients in 18 HIV reference centres in France were prospectively included in the Dat'AIDS cohort. Data were collected from all patients starting an INSTI-containing regimen between 1 January 2006 and 31 December 2016. All causes of INSTI-containing regimen discontinuations were analysed, and patients' characteristics related to discontinuation due to NPAEs were sought. Results: INSTIs were prescribed to 21315 patients: 6274 received dolutegravir, 3421 received elvitegravir boosted by cobicistat, and 11620 received raltegravir. Discontinuation was observed in 12.5%, 20.2% and 50.9% of the dolutegravir-, elvitegravir- and raltegravir-treated patients, respectively ( P < 0.001). Discontinuation for NPAEs occurred in 2.7%, 1.3% and 1.7% of the dolutegravir-, elvitegravir-, and raltegravir-treated patients, respectively ( P < 0.001). In the multivariate analysis, discontinuation for NPAEs was related to dolutegravir versus elvitegravir (HR = 2.27; 95% CI 1.63–3.17; P < 0.0001) and versus raltegravir (HR = 2.46; 95% CI 2.00–3.40; P < 0.0001), but neither gender (HR for women = 1.19; 95% CI 0.97–1.46; P = 0.09) nor age ( P = 0.12) was related. The association with abacavir was not retained in the final model. Conclusions: Although discontinuation for side effects was less frequent with dolutegravir than with boosted elvitegravir, discontinuation for NPAEs, although rare (2.7%), was more frequent with dolutegravir. No patient characteristic was found to be associated with these side effects in this very large population.